How customers construct corporate social responsibility images: Testing the moderating role of demographic characteristics - Andrea Pérez; Ignacio Rodríguez del Bosque (BRQ Business Research Quarterly, 2015)
Summary This paper discusses the formation process of CSR images from a customer perspective. It analyses the influence of company-CSR coherence, motivational attribution and corporate credibility in the way customers evaluate CSR images in the banking industry. It also describes the impact of customer gender, age and educational level on the formation of CSR images. Results show that CSR images are based on customer perceptions of the company-CSR coherence, the attribution of altruistic motivations and corporate credibility when developing CSR initiatives. The findings also demonstrate that gender, age and educational level do not allow identifying differences in the way customers construct CSR images. Thus, they are not useful in segmenting customers for the design of better CSR and communication strategies."
Keywords: 650; CSR image; Gender; Age; Educational level; Segmentation